The Effect of Providing Ultrafine Nanobubbles (UFB) Liquid Organic NPK Fertilizer on the Growth of Pueraria javanica Plants in Ex-Coal Mining Land Areas - Hazqan Hari Asri; Abdul Razak; Nurhasan Syah; Skunda Diliarosta; Muhamad Sholichin (Jurnal Penelitian Pendidikan IPA, 2025)
One of the main challenges in the reclamation process of former coal mining land is low soil fertility. Common soil characteristics found in former mining land include unbalanced pH, low organic matter content, poor soil structure, and minimal availability of nutrients. This makes it difficult for plants to grow and develop optimally in former mining land areas. This type of research is an experimental research with a Research Design using a Completely Randomized Design (CRD) 4 x 6. The population of this study was all Ruji Bean Plants (Pueraria javanica) growing in the Wire House area of PT. Pacific Coal Mining with a sample of this study of 24 Ruji Bean Plants (Pueraria javanica). The results of this study are that the provision of UFB Organic NPK fertilizer has been proven to help improve soil conditions. The dosage of UFB liquid organic NPK fertilizer solution for optimal Ruji Bean plant growth is in treatment 4 with a dose (90 ml). In terms of economy, the production of UFB liquid organic NPK fertilizer is IDR 40,300/liter, while the price of liquid NPK fertilizer on the market is IDR 100,000/liter. So, the use of UFB liquid organic NPK fertilizer solution can be a good choice for reclamation activities, this can save fertilization costs for post-mining land reclamation activities and is environmentally friendly because UFB liquid organic NPK fertilizer is made from organic materials.